On Commutative Systems of Nonselfadjoint Unbounded Linear Operators - Zolotarev, V.A. (Журнал математической физики, анализа, геометрии, 2009)
For a commutative system of nonselfadjoint unbounded operators A₁, A₂ the concept of colligation and associated open system is given. For these open systems, the consistency conditions are established and the conservation laws are obtained.